Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858224
|View full text |Cite
|
Sign up to set email alerts
|

When Tablets meet Tabletops

Abstract: Cross-device collaboration with tablets is an increasingly popular topic in HCI. Previous work has shown that tabletonly collaboration can be improved by an additional shared workspace on an interactive tabletop. However, large tabletops are costly and need space, raising the question to what extent the physical size of shared horizontal surfaces really pays off. In order to analyse the suitability of smaller-thantabletop devices (e.g. tablets) as a low-cost alternative, we studied the effect of the size of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For example, early observations of multi-display use in office environments [112] triggered other research of how cognitive load can be reduced through usage of multiple displays [153] and multiple devices [75,252,290]. Similarly, other observational studies have been used to investigate current multi-device utilisation [41,42], barriers for true multi-device usage [263], or the effects of display sizes in collaborative work [148,377].…”
Section: Evaluation Through Demonstrationmentioning
confidence: 99%
“…For example, early observations of multi-display use in office environments [112] triggered other research of how cognitive load can be reduced through usage of multiple displays [153] and multiple devices [75,252,290]. Similarly, other observational studies have been used to investigate current multi-device utilisation [41,42], barriers for true multi-device usage [263], or the effects of display sizes in collaborative work [148,377].…”
Section: Evaluation Through Demonstrationmentioning
confidence: 99%
“…Some approaches also combine tablets for personal use with tabletops [34,53,57]. Recent work, however, has found that users are also able to efficiently collaborate without large shared displays and only with tablet-sized devices [57].…”
Section: Multi-device and Cross-device Interactionmentioning
confidence: 99%
“…[2,6,21,22,45]) can mediate collaborative sensemaking activities. In particular, such setups can provide a shared display [6,33,45] and collaboration space [2,40], support spatial and visual organization of content [49], provide awareness [9,43], and support a shared understanding [22,45]. However, recent studies suggested that an increased size of a shared space is not indicative of improved collaborations, as participants' attention may be diverted towards the screen instead of other collaborators [49], and that users are hesitant to use multiple tablets in parallel, hinting at a "legacy bias" to use tablets as computers rather than documents [32].…”
Section: Shared Spaces For Collaboration In Multi-device and Large Scmentioning
confidence: 99%